Perspective Effects During Reading: Evidence from Text Change-Detection. Issue 2 (17th February 2018) - Bohan, Jason; Filik, Ruth
ABSTRACT: We report two text change-detection studies in which we investigate the influence of reading perspective on text memory. In Experiment 1 participants read from the perspective of one of two characters in a series of short stories, and word changes were either semantically close or distant. Participants correctly reported more changes to perspective-relevant than perspective-irrelevant words and for distant than close changes. However, distance and perspective did not interact, suggesting that adopting a particular perspective did not lead to a more fine-grained analysis of perspective-relevant information. In Experiment 2 participants read one long narrative from the perspective of either a burglar or house-buyer. Results showed that only participants with a low working memory span showed perspective effects, suggesting that individual differences in working memory capacity appear to influence processing of perspective-relevant information.